AB0539 Correlation between morphological and functional microvascular damage in systemic lupus erythematosuspatients. (12th June 2018) - Sulli, A.; Ruaro, B.; Pizzorni, C.; Smith, V.; Paolino, S.; Pendolino, M.; Verni, L.; Cutolo, M.
Abstract : Background: Numerous articles have investigated peripheral microcirculation in primary Raynaud's phenomenon (PRP). 1–3 However, reports that analyse peripheral microcirculation in systemic lupus erythematosus (SLE) are scanty. 4 5 Objectives: The aim of this study was to investigate possible correlations between morphological and functional aspects of microcirculation in different skin areas of the hands and face in SLE patients and to compare the results with PRP patients and healthy subjects (HS). Methods: A total of 14 SLE patients without RP (ACR criteria) 6 (mean age 53±14 SD years, mean disease duration 7±4 years), 14 PRP patients (LeRoy and ACR/EULAR 2013 criteria) 7 8 (mean age 53±17 years, mean RP duration 6±5 years) and 14 HS (mean age 50±17 years) were enrolled during the winter period. Nailfold videocapillaroscopy (NVC) and laser speckle contrast analysis (LASCA) were performed in the three groups of patients. The absolute nailfold capillary number (CN) per linear millimetre at first distal row was assessed by NVC. Blood perfusion (BP) was detected by LASCA at the level of fingertips, periungual areas, dorsum and palm of both hands and face. The average BP was calculated as perfusion units (PU). 2 Patients were not taking vasodilator drugs since at least one month. Statistical analysis was performed by non parametric tests. Results: SLE patients showed a positive correlation between BP and nailfold CN in all areas of hands (p<0.0001), but no statistically significant correlation was observed between BP and nailfold CN at the level of face (p=0.10). In both PRP and HS no statistically significant correlation was observed between BP and nailfold CN in all examined areas (p=0.70 and p=0.20, respectively). SLE patients showed a statistically significant lower nailfold CN than both PRP and HS (median 9.1 vs 10.3 vs 11.0, respectively, p<0.0005). Conversely, no statistically significant difference of nailfold CN was observed between PRP and HS. PRP patients showed a statistically significant lower BP than both SLE and HS at the level of fingertip (median 90, 114, 187 PU, respectively; p<0.0001), periungual (median 74, 100, 141 PU, respectively, p<0.0001), dorsal (median 61, 72, 128 PU, respectively, p<0.0001), and palm areas (median 76, 96, 124 PU, respectively, p<0.0001). Conversely, PRP, SLE and HS patients showed similar BP values at the level of face (median 141, 139, 137 PU, respectively, p=0.30). Conclusions: This study demonstrates a correlation between morphological and functional microvascular features in SLE patients. SLE patients without RP have a subclinical microangiopathy, showing lower nailfold CN and BP than HS. Conversely, PRP patients show only a functional dysfunction, having a lower peripheral skin BP than both SLE patients and HS. The clinical value of this new finding is undergoing further analysis. References: [1] Cutolo M, et al. J Rheumatol2010;37:1174–80. [2] Ruaro B, et al. Ann Rheum Dis2014;73:1181–5. [3] Rosato E, et al. Rheumatology2009;36:2257–63. [4] Anania C, et al. Lupus2012;21:815–20. [5] de Leeuw K, et al. Lupus2008;17:1010–1017. [6] Petri M, et al. Arthritis Rheum. 2012;64:2677–86. [7] van den Hoogen F, et al. Ann Rheum Dis2013;72:1747–55. [8] LeRoy EC, et al. Clin Ex Rheumatol1992;10:485–8. Disclosure of Interest: None declared